COD fractions in mechanical-biological wastewater treatment plant = Frakcje ChZT w mechaniczno-biologicznej oczyszczalni ścieków - Płuciennik-Koropczuk, Ewelina; Jakubaszek, Anita; Myszograj, Sylwia; Uszakiewicz, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents results of studies concerning the designation of COD fraction in the raw, mechanically treated and biologically treated wastewater. The test object was a wastewater treatment plant with the output of over 20,000 PE. The results were compared with data received in the ASM models.
Keywords: wastewater; COD fractions; ASM models; organic substances biodegradable; organic substances non-biodegradable; ścieki; frakcje ChZT; modele ASM; substancje organiczne biodegradowalne; substancje organiczne niebiodegradowalne